Entrepreneurial Culture and Impediments to its Dissemination as Perceived by Elemantary-School Science Teachers in Irbid, Jordan - Alshorman, Sameera (Dirasat: Educational Sciences, 2024)
Objectives: The current study aims to investigate the entrepreneurial competencies of elementary-school science teachers in Irbid and to examine the impediments to the incorporation of entrepreneurial education as perceived by the teachers. Methods: The study sample consists of (100) teachers, evenly distributed between males and females, with (50) teachers in each group. To achieve the study’s objectives, a questionnaire consisting of (52) items was developed, divided into two main sections: the first section focuses on the current entrepreneurial competencies of the teachers, encompassing three dimensions: the first dimension (entrepreneurial knowledge) comprises (14) items, the second dimension (entrepreneurial skills and traits) comprises (14) items, and the third dimension (ideas and attitudes) comprises (12) items. The second section, which consists of (12) items, addresses impediments to the incorporation of entrepreneurial education. Results: The results indicate a moderate level of entrepreneurship based on that teachers’ response to the first section. Moreover, statistically significant differences were observed based on their responses to the third dimension, favoring male teachers. Additionally, the study shows that teachers’ viewpoints regarding the impediments to the incorporation of entrepreneurship education vary, as their responses to the items of the second section rang from high to low. Conclusions: Based on the results, the study recommends developing an entrepreneurial culture among elementary-school science teachers through awareness brochures, training courses, and workshops. It also calls for further research to examine the incorporation of an entrepreneurial education into school curricula.